2012
DOI: 10.1134/s1064562412020123
|View full text |Cite
|
Sign up to set email alerts
|

On affine reducibility of combinatorial polytopes

Abstract: 283This paper considers families of combinatorial polytopes for which the problem of recognizing the nonadjacency of two arbitrary vertices is NP com plete. It is shown that all such polytopes contain spe cial 0/1 programming problems as faces, for which the problem of recognizing the nonadjacency of verti ces is NP complete too.A combinatorial polytope is usually specified as fol lows. Consider a set X ⊆ {0, 1} d of vertices of the d dimensional 0/1 cube satisfying certain constraints, specific for each probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…That is 3 ∝ 3AP in the sense of relation ≤ . However, from inequality (17), theorem 9, theorem 13 and DCP ∝ 3 [21] it follows that the reduction 3 ∝ 3AP is impossible. Now we show, that SSP ∝ 3AP.…”
Section: Three Index Assignment Polytopesmentioning
confidence: 99%
See 3 more Smart Citations
“…That is 3 ∝ 3AP in the sense of relation ≤ . However, from inequality (17), theorem 9, theorem 13 and DCP ∝ 3 [21] it follows that the reduction 3 ∝ 3AP is impossible. Now we show, that SSP ∝ 3AP.…”
Section: Three Index Assignment Polytopesmentioning
confidence: 99%
“…Relying on definitions 1 and 3, we can introduce an analogue of Cook-Karp-Levin polynomial reducibility [14] for families of polytopes (as it was done in [21]).…”
Section: Affine Reducibility and Boolean Quadratic Polytopesmentioning
confidence: 99%
See 2 more Smart Citations
“…In [22,26] it was shown that so-called double covering polytopes are affinely reduced to knapsack polytopes, set covering polytopes, cubic subgraph polytopes, 3-SAT polytopes, partial order polytopes, and traveling salesman polytopes. The linear optimization on double covering polytopes is NP-hard and the problem of checking nonadjacency on these polytopes is NP-complete [27].…”
Section: Introductionmentioning
confidence: 99%